Nilai Nasionalisme dalam Hikayat Perang Sabil Teungku Chik Pantee Kulu - Syamsul Rizal (At-Tafkir, 2021)
This article discusses nationalism in the sabil war saga written by Teungku Chik Pantee Kulu. The sabil war saga written by Tengku Chik Pantee Kulu is a saga found in Acehnese society and can give the spirit of defending the country after listening to it. This saga was written in 1873 after he returned from Mecca and at that time Aceh fought against the Dutch. This research method uses literature study with a hermeneutic approach. The primary data source is Ali Hasjmy's book, Aceh Literary Contributions in the Development of Indonesian Literature, Jakarta: Bulan Bintang, 1977. The results of the analysis show that there are five values of nationalism in the sabil war saga by Teungku Chik Pante Kulu, namely love for the homeland, self-sacrifice, interest country above personal interests, has a heroic spirit, and does not give up easily.